Doping in sport and fitness - Henning, April; Andreasson, Jesper (Research in the sociology of sport ;, 2022)
Doping, as both practice and phenomenon, has largely been approached as a question of socio-cultural context and structures. Doping in Sport and Fitness argues that rigid differentiations between doping contexts - such as sport/fitness or elite/recreational - are less clear than it might seem. Breaking down these boundaries allows for a more complete understanding of substance use patterns, behaviours, and policy responses related to sport, fitness, and society. Contextual separations have greatly impacted how scholars have addressed the phenomena of doping in contemporary society, which in turn has impacted current anti-doping policies, preventative work, and harm reduction strategies globally. Bringing together research on doping and image and performance enhancement drug use (IPED) that highlights links between areas of doping research that have been previously separated, this collection includes contributions focusing on emerging and under-researched topics related to IPED use. Providing studies on new demographic groups of users, especially in terms of gender and age, Doping in Sport and Fitness suggests alternative ways of approaching the issue and supports providers such as coaches and drug service professionals.